Spontaneous rupture of the umbilical vein associated with liver cirrhosis: A case report. (August 2021) - Honmyo, Naruhiko; Kohashi, Toshihiko; Hakoda, Keishi; Oishi, Koichi; Nakashima, Akira; Shintakuya, Ryuta; Hihara, Jun
Abstract: Introduction: A decompensated cirrhosis sometimes develops collateral circulation due to severe fibrosis. Rupture of this collateral circulation can induce a fatal situation. Case presentation: A 59-year-old man with alcoholic cirrhosis was admitted to our emergency department with a chief complaint of impaired consciousness. The patient had hypotension upon arrival, and enhanced computed tomography (CT) revealed a massive hemoperitoneum. Imaging examinations, including interventional radiography, could not identify the source of bleeding preoperatively; therefore, emergency surgery was performed. Intraoperatively, a collapsed small vessel connecting liver segment 4 and the expanded umbilical vein as collateral circulation due to portal hypertension was detected as the source of bleeding. Ligating the stump of the small vessel and postoperative intensive care saved the patient's life. The patient was discharged from our hospital 14 days after the surgery. Clinical discussion: A rupture of the umbilical vein associated with cirrhosis is rare and causes a critical situation because of the fast blood flow in the collateral circulation caused by portal hypertension. Moreover, the amount of bleeding tends to increase since the abdominal cavity is a free space and patients with cirrhosis have coagulopathies, including thrombocytopenia and prolonged prothrombin time. Although a retrospective review of the enhanced CT image could identify the minute findings, arterial portography was insufficient to detect bleeding from the umbilical vein. Therefore, emergency exploratory laparotomy was required for the diagnosis and treatment. Conclusion: Rupture of the reopened umbilical vein can cause idiopathic spontaneous hemoperitoneum in patients with decompensated cirrhosis. Highlights: A rupture of the umbilical vein due to cirrhosis can induce fatal hemoperitoneum. Interventional radiology could not detect the source of bleeding. Emergency surgery is required for idiopathic hemoperitoneum in liver cirrhosis.